Pengelolaan Keuangan Guna Menghadapi Resesi 2023 - Astari Dianty (Jurnal Bhakti Karya dan Inovatif, 2023)
The threat of a global recession is projected to continue until 2023, where this starts in 2021 due to the impact of Covid-19, GDP has decreased to decline in successive quarters. This should not be ignored because it will have an impact on the possibility of increasing the risk of recession. . So that business people are not significantly affected by the 2023 recession which is projected to continue, business people must have financial quality that is strong enough both now and in the future. This can be realized through good financial management. The implementation method for this activity consisted of a preparatory stage, namely conducting an initial survey of the Bojongloa District regarding the problems that occurred, carrying out sharing sessions on financial management, and conducting monitoring and evaluation to find out how much the participants' abilities in this financial management activity had increased.